DESIGN AND ANALYSIS OF POTENTIAL LATERAL BUCKLING FAILURE ON OFFSHORE PIPELINE IN MUARA KARANG, WEST JAVA - G.D. Simanjuntak, Samuel
In supporting oil and gas exploration and exploitation activities, it is necessary to have facilities and infrastructure to be able to facilitate these activities. One of the facilities that can support oil and gas exploration and exploitation activities is the subsea pipeline. Before the subsea pipeline is used for exploration activities, it is necessary to make a detailed plan of the strength and feasibility of the pipeline. With the design and analysis process, it is expected that the subsea pipeline can withstand different loads and meet the feasibility standards during the pipeline operation. The design process begins with the design of the pipe wall thickness by the DNVGL-ST-F101 standard, design of on-bottom stability using the DNVGLRP- F109 standard, installation analysis by industrial practical design criteria, or criteria based on DNVGL-ST-F101, and free span design using the DNVGL-RPF105 standard. In the next stage, thermal end expansion analysis design is carried out, to determine the increase in pipe length due to the pipe constituent material reacting to temperature and pressure differences. Then an analysis of potential lateral failures of buckling is carried out using the Hobbs method. Based on the design process carried out in this Final Project, the wall thickness of the pipe that will be used is 12.7 mm (0.5 in), and the thickness of the concrete layer is 40 mm (1.5748 in). Then, based on the analysis of the installation with the configuration of trim angles and hitch 0°, the highest value of the stress on the pipeline was 82.73% SMYS at the dynamic analysis at maximum depth with a wayward directional angle of 163.61, with residual stress of 605.44 kN. Subsequently, the maximum free span that can occur on the pipeline amounted to 18.74 m was obtained. In the thermal expansion analysis, it was found that the pipe will elongate by 7 mm during hydrotest conditions, 214 mm during operating conditions, and by 118 mm during shut down conditions. The results of the follow-up analysis stated that the pipeline that has been designed did not have the potential to experience lateral buckling failure because the axial load was not large enough to trigger the failure.